Skeletal Muscles Injury Related to SARS-CoV-2 Infection: A Case Report - Laksmidewi, Anak Agung Ayu Putri; Gabur, Maria Oktaviany; Indah, Carolin Tiara Lestari (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Coronavirus disease 2019 (COVID-19) is a disease related to coronavirus (SARS-CoV-2) which is categorized as Nidovirales order, family beta-coronaviridae. Coronavirus infects mainly the lung as well as other organs out of the lung. Extrapulmonary infection includes neurological infection such as the central nervous system, peripheral nervous system, and musculoskeletal with various symptoms. Recent study reported that 30% of patients had COVID-19-associated skeletal muscle injury. CASE PRESENTATION: A 78-year-old male with a history of stroke and Type 2 diabetes mellitus came to the emergency department with fever, shortness of breath, decrease of consciousness, joints, and muscles pain. Chest X-ray showed a consolidation in the mid-lower of the lung bilaterally, with prominent bronchovascular markings, polymerase chain reaction COVID-19 result comes out with positive 2 times with 10 days interval. The patient is treated with antibiotics, Avigan, azithromycin, and high-dose intravenous Vitamin C. In the 3rd ward day, the patient still has short of breathiness. However, fever and consciousness improve, but still complaining of pain in the shoulder joint, arm muscles, and knee joint. On the 11th inpatient day, the patient obtains full consciousness; dyspnea improved, no fever, however, the patient still complains of muscle and joint pain. At the end of the inpatient period fever, dyspnea and consciousness seem to be improved; however, the patient still complains of pain in the shoulder joint, arm muscles, and knee joint that not improved with an analgesic. The patient comes back to his home in good condition. CONCLUSION: COVID-19 patients may develop musculoskeletal symptoms such as skeletal injury or myalgia, and this is our first case of COVID-19 infection complicated with skeletal muscle injury.